2006
DOI: 10.1080/14445921.2006.11104201
|View full text |Cite
|
Sign up to set email alerts
|

Expert System Portfolios of Australian and UK Securitised Property Investments

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In other hand, rule-based ES is a computer program that is capable to use information in a knowledge base, using a set of inference procedures, to solve problems that are difficult enough to require significant human expertise for their solution [124]. The set of inference procedures are provided by a human expert in the particular area of interest, while the knowledge base is an accumulation of relevant data, facts, judgments and outcomes [125]. ES consists of three main components including the knowledge base, the inference engine and the user interface.…”
Section: Expert System Applications In Financial Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…In other hand, rule-based ES is a computer program that is capable to use information in a knowledge base, using a set of inference procedures, to solve problems that are difficult enough to require significant human expertise for their solution [124]. The set of inference procedures are provided by a human expert in the particular area of interest, while the knowledge base is an accumulation of relevant data, facts, judgments and outcomes [125]. ES consists of three main components including the knowledge base, the inference engine and the user interface.…”
Section: Expert System Applications In Financial Domainmentioning
confidence: 99%
“…This system helps investment decision maker and project analysts to choose a project for their investing portfolio. In another study, [125] designed an ES for portfolios of Australian and UK securitized property investments. They concluded that their proposed expert system outperforms general property market and randomly selected portfolios in select cases, although the outperformance was not statistically significant.…”
Section: Portfolio Managementmentioning
confidence: 99%
“…artificial intelligent algorithms and rough sets). Recently, artificial intel- ligent methods (specially ANN) are the most popular tool used for credit scoring and has been reported that its accuracy is superior to that of traditional statistical methods in dealing with credit scoring problems, especially in regards to nonlinear patterns [29,31,35,60]. In this paper we used two famous artificial intelligence algorithms i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In other hand, rulebased expert system is a computer program that is capable of using information contained in a knowledge base, along with a set of inference procedures, to solve problems that are difficult enough to require significant human expertise for their solution [34]. The set of inference procedures are provided by a human expert in the particular area of interest, while the knowledge base is an accumulation of relevant data, facts, judgments and outcomes [35]. As illustrated in Fig.…”
Section: Expert Systemmentioning
confidence: 99%
“…In that research, Ellis and Wilson find neural network constructed domestic real estate portfolios outperformed a general securitized property market benchmark captured by both the ASX 300 property market index and a property market index constructed by Datastream International. While Ellis and Wilson (2006) use a rule based expert system to examine international diversification from an Australian investor's perspective, the present article appears to be the first to use a neural network model to examine the benefits of international diversification of real estate assets.…”
Section: Introductionmentioning
confidence: 99%